Prosopis juliflora pods mash for biofuel energy production: Implication for managing invasive species through utilization - Haile, Mebrahtu; Hishe, Hadgu; Gebremedhin, Desta (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
Fuels obtained from renewable resources have merited a lot of enthusiasm amid the previous decades mostly because of worries about fossil fuel depletion and climate change. The aim of this study was to investigate the potential of Prosopis juliflora pods mash for bio-ethanol production and its hydrolysis solid waste for solid fuel. Parameters such as acid concentration (0.5 - 3 molar), hydrolysis times (5-30 min), fermentation times (6-72h), fermentation temperature (25 OC - 40 OC) and pH (4-8) on bio-ethanol production using Saccharomyces cerevisiae yeast were evaluated. Results show that the content of sugar increases as the acid concentration (H2SO4) increased up to 1 molar and decreases beyond 1 molar.Â A maximum sugar content of 96.13 %v/v was obtained at 1 molar of H2SO4 concentration. The optimum conditions for bio-ethanol production were found at 1 molar of H2SO4 concentration (4.2 %v/v), 48 h fermentation time (5.1%v/v), 20 min hydrolysis time (5.57 %v/v), 30 OC fermentation temperature (5.57 %v/v) and pH 5 (6.01 %v/v). Under these optimum conditions, the maximum yield of bio-ethanol (6.01%v/v) was obtained. Furthermore, the solid waste remaining after bio-ethanol production was evaluated for solid fuel application (18.22 MJ/kg). Hence, the results show that Prosopis juliflora pods mash has the potential to produce bio-ethanol. The preliminary analysis of solid waste after hydrolysis suggests the possibility to use it as a solid fuel, implying its potential for alleviating major disposal problems.Article History: Received March 24th 2018 ; Received in revised form September 15th 2018; Accepted October 1st 2018; Available onlineHow to Cite This Article: Haile, M., Hishe, H. and Gebremedhin, D. (2018) Prosopis juliflora Pods Mash for Biofuel Energy Production: Implication for Managing Invasive Species through Utilization. International Journal of Renewable Energy Development, 7(3), 205-212.https://doi.org/10.14710/ijred.7.3.205-212Â